Dynamic changes in depolarization of action potentials by high frequency stimulation in guinea pig papillary muscles - Shen Wei-qun; Xu Xin-yi; Zhao Wei-wei; Duan-mu Zhao-xia; Yu Zhi-min; Yu Xian-min; Wang Lu-yang; Zhang Lu-yong (Acta Pharmacologica Sinica; Vol 10, No 4 (July 1989): Acta Pharmacologica Sinica, 2016)
The effect of high frequency stimulation on rate-dependent depression of depolarization of action potentials was studied with computer and standard microelectrode techniques in guinea pig papillary muscles. After increasing driving frequency from 0.5 to 6 Hz, decreases in Vmax, APA and OS were found. Changes of upstroke velocity during phase 0 between driving frequency 6 and 0.5 Hz could be described as a parabola. The rate-dependent depression of depolarization was exaggerated by tetrodotoxin (TTX), particularly during the accelerating period of phase 0. A progressive decline in Vmax, which could be fitted by a power function curve, was observed after changing driving frequency from 1 to 5 Hz. TTX significantly influenced the decline in Vmax and the regression coefficients in fitted equations.